Alelopatia de carqueja (Baccharis trimera Less) e ação de fungos em capim-annoni (Eragrostis plana Ness) - Gonçalves, Carlos Eduardo Prates (2014)
Livestock in southern Brazil is sustained largely by native pastures, which have large species diversity. This area is part of the Pampa biome. However, invasive species Eragrostis plana (tough lovegrass) threat to native grasslands of this biome. Becomes necessary to develop alternative methods of control of this species, since conventional control practices, although fairly efficient, has no as a principle the preservation of native vegetation. The present work aimed to study the control of tough lovegrass through biocontrol method for isolation of potentially pathogenic fungi, as well as the allelopathic effects of aqueous extract of carqueja (Baccharis trimera) on the germination of tough lovegrass. The fungi were isolated from seeds of tough lovegrass and incubated for eight days of growth at 25 °C and a photoperiod of 12 hours, then identified to genus chamber. Five genera were identified: Alternaria sp., Curvularia sp., Aspergillus sp., Penicillium sp. e Fusarium sp. To test the interaction of these fungi with the seeds of E. plana, fungi inoculation was performed in seeds through deposition technique, which were previously sterilized with 1% NaClO, and seeded on two types of substrates: filter paper (in vitro experiment) and substrate and sand mixture (ex vitro experiment). Treatments consisted of the five identified fungi, inoculated separately in seeds of E. plana. The genera showed that the best results were: Fusarium sp., Curvularia sp. e Penicillium sp. The carqueja belongs to the Asteraceae family, possessing compounds with many properties. Among the compounds present in B. trimera can highlight the presence of flavonoids, tannins, fatty acids, steroids, triterpenoids. To evaluate the allelopathic effect of B. trimera on E. plana different doses of the crude aqueous extract (CAE) of carqueja were applied on the seeds of tough love-grass. The concentrations where 0; 25; 50; 75 and 100 g.L-1. The experiments were conducted in vitro and ex vitro. The High-performance liquid chromatography (HPLC) was also conducted to identify the compounds present in the CAE. Were found in larger amounts: caffeic acid, chlorogenic acid, ellagic acid and isoquercitina. In the in vitro experiment the inhibition of the germination appeared from the concentration of 25 g.L-1 upwards, causing a diminishing germination with increasingly higher concentrations of the CAE. In the ex vitro experiment the reduction of emergence was lower, but was statistically significant. The data show that the carqueja extracts interfere on the development of the tough lovegrass by reducing leaf length and the dry mass of the aerial part and of the roots.